PENGARUH MODEL DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS VIII SMP NEGERI 31 PADANG - Khatrin, Khatrin; Abdurrahman, Abdurrahman (Universitas Negeri Padang, 2020)
ABSTRACT The purpose of this research was to describe things as follow. First, describes the writing skills of the exposition text of grade VIII Junior High School 31 Padang before using the discovery learning model. Secondly, describes the writing skills of the exposition text of grade VIII Junior High School 31 Padang after using the discovery learning model. Third, analyze the effect of discovery learning models on the exposition writing skills of grade VIII studensts of Junior High School 31 Padang. The type of this research is quantitative research using experimental methods Based on the results of the study, can be concluded three things as follows. First, the writing skills of the exposition text of grade VIII students of Junior High School 31 Padang before using discovery learning model are in fair qualifications (61,59). Secondly, the writing skills of exposition text of grade VIII students of Junior High School 31 Padang after using discovery learning model are in good qualifications (78,26). Third, there is a significant influence in the use of discovery learning models on the exposition writing skills of grade VIII students of Junior High School 31 Padang, so it can be concluded that H1 is accepted in H0 is rejected because the test results prove that tcount is greater than ttable (2,04>1,70). Kata Kunci: Pengaruh, Model Discovery Learning, Menulis Teks Eksposisi